2014
DOI: 10.1186/1423-0127-21-56
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification for epigallocatechin-3-gallate-mediated antioxidant intervention on the H2O2-induced oxidative stress in H9c2 rat cardiomyoblasts

Abstract: BackgroundEpigallocatechin-3-gallate (EGCG) has been documented for its beneficial effects protecting oxidative stress to cardiac cells. Previously, we have shown the EGCG-mediated cardiac protection by attenuating reactive oxygen species and cytosolic Ca2+ in cardiac cells during oxidative stress and myocardial ischemia. Here, we aimed to seek a deeper elucidation of the molecular anti-oxidative capabilities of EGCG in an H2O2-induced oxidative stress model of myocardial ischemia injury using H9c2 rat cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…EGCG has shown to exert such activity by influencing cellular signal transduction pathways and reactive oxygen species [38,39]. Previous studies have shown that gallate esters are important for the association of polyphenols with proteins, probably because they mediate weak hydrophobic interactions with proline-rich regions in target proteins, which is a prerequisite for subsequent hydrogen bond formation [40].…”
Section: Implication Of Therapeutic Strategy For Neurodegenerative DImentioning
confidence: 99%
“…EGCG has shown to exert such activity by influencing cellular signal transduction pathways and reactive oxygen species [38,39]. Previous studies have shown that gallate esters are important for the association of polyphenols with proteins, probably because they mediate weak hydrophobic interactions with proline-rich regions in target proteins, which is a prerequisite for subsequent hydrogen bond formation [40].…”
Section: Implication Of Therapeutic Strategy For Neurodegenerative DImentioning
confidence: 99%
“…EGCG is the most physiologically potent compound, and primarily accounts for the biological effects of green tea [ 2 ]. Studies with a cell line of H9c2 rat cardiomyoblasts associated with H 2 O 2 - induced oxidative stress also demonstrated the protective role of EGCG against oxidative injury and cell death caused by ROS and cytosolic Ca 2+ overload in cardiac cells [ 29 - 31 ].…”
Section: Anti-oxidative Capacities Of Gtpsmentioning
confidence: 99%
“…The convergence of these pathways via inhibition of GSK-3β on the end effector to limit mPTP induction is the general mechanism of cardiomyocyte protection [ 52 ]. Recent reports also provided evidence for that the cardio-protection of GTPs against oxidative stress associated with myocardial ischemic injury is caused by reducing cytosolic Ca 2+ overload and generation of ROS via the Akt/GSK-3β/β-catenine and caveolae signaling both in vivo myocardial ischemia injury [ 13 , 14 ] and In vitro H 2 O 2 -induced oxidative stress models [ 29 - 30 ].…”
Section: Gtps Mediated Cardiac Protection Against Myocardial Ischementioning
confidence: 99%
See 2 more Smart Citations